Image Enhancement for Characterization of MinD Protein Oscillation in Escherichia coli - Kanthang, Paisan (Applied Mechanics and Materials, 2017)
MinD proteins play important roles during cell division process. These proteins show significant characteristics of periodic pole-to-pole propagation along the cell length. The characterizations of these protein behaviors are required to be determined accurately. Usually by using a fluorescent technique, visual motion of proteins in the cell could possibly be made and observed through a CCD. Due to the nature of low intensity of these proteins, the images obtained from the CCD camera were required to subject to noise interference and as a result digital image processing was also required. In this paper, several techniques were tried to facilitated improve the image quality. From our finding, the fluorescent technique could affect the intensity fading of the protein detected, but not to the numbers of the proteins in the cell.